PENGARUH MODEL PEMBELAJARAN INQUIRY BERBASIS GOOGLE CLASSROOM TERHADAP HASIL BELAJAR GEOGRAFI KELAS XI IPS DI SMA NEGERI 1 MEUKEK - Syam, Indah Sukma; Aziz, Daska; Furqan, Muhammad Hafizul (Jurnal Ilmiah Mahasiswa Pendidikan Geografi, 2025)
The lack of optimization in the teaching models used by teachers has led to low student learning outcomes. This is evident from students' difficulties in answering exam questions, which affect their learning efficiency and performance. Selecting an appropriate teaching model is crucial for enhancing students' understanding of the material. This study aims to determine the effect of the inquiry-based learning model using Google Classroom on the geography learning outcomes of 11th-grade social science students at SMA Negeri 1 Meukek. This research employs a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study population consists of 11th-grade students, with purposive sampling selecting class XI IPS 1 as the experimental group and XI IPS 2 as the control group. Data was collected through multiple-choice tests, while data analysis techniques included normality tests, homogeneity tests, and hypothesis testing. The results showed that the average pre-test and post-test scores for the experimental class were 50.5 and 77.25, while the control class scored 48.5 and 72.5, respectively. The t-test results indicated that tcount = 2.07 was greater than ttable = 1.68, leading to the acceptance of Ha. Thus, the inquiry-based learning model using Google Classroom is proven to be more effective in improving student learning outcomes compared to the small group discussion model. Therefore, this model can be considered an alternative for geography learning to enhance students' understanding and academic achievement.Kurangnya optimalisasi model pembelajaran yang digunakan oleh guru menyebabkan rendahnya hasil belajar siswa. Hal ini terlihat dari kesulitan siswa dalam menjawab soal ujian, yang berdampak pada efisiensi dan hasil belajar mereka. Pemilihan model pembelajaran yang tepat sangat penting untuk meningkatkan pemahaman siswa terhadap materi. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran inquiry berbasis Google Classroom terhadap hasil belajar geografi siswa kelas XI IPS di SMA Negeri 1 Meukek. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis quasi eksperimen dan desain nonequivalent control group design. Populasi penelitian adalah siswa kelas XI, dengan teknik purposive sampling yang menentukan kelas XI IPS 1 sebagai kelas eksperimen dan XI IPS 2 sebagai kelas kontrol. Pengumpulan data dilakukan melalui tes pilihan ganda, sedangkan teknik analisis data meliputi uji normalitas, homogenitas, dan uji hipotesis. Hasil penelitian menunjukkan bahwa rata-rata nilai pre-test dan post-test kelas eksperimen adalah 50,5 dan 77,25, sedangkan kelas kontrol 48,5 dan 72,5. Hasil uji-t menunjukkan thitung = 2,07 lebih besar dari ttabel = 1,68, sehingga Ha diterima. Dengan demikian, model pembelajaran inquiry berbasis Google Classroom terbukti lebih efektif dalam meningkatkan hasil belajar siswa dibandingkan dengan model diskusi kelompok kecil. Oleh karena itu, model ini dapat dijadikan sebagai alternatif dalam pembelajaran geografi untuk meningkatkan pemahaman dan prestasi siswa.